OIL SARDINE FISHERY AT KOZHIKODE DURING THE SEASONS 1959-60 to 1962-63 - Prabhu, M S (Indian Journal of Fisheries, 2011)
The oil sardine fishery at Kozhikode showed an upward trend from1959-60 to 1961-62 followed by a decline in 1962-63. Non-selective gears,namely, Pattenkolli vala, Mathikolli vala, Thattum vala and Nethel vala (allboat-seines) were the main gears which accounted for the major part of theoil sardine landings. Variations in the quarterly and annual catch-per-net andcatch-per-unit of effort of the different gears have been discussed. The fisherywas confined mostly to the October-December quarter when generally sizegroups ranging from 105 to 149 mm contributed to the bulk of the landings.From the occurrence and progression of the different modes it was inferredthat the fishery is dependent on more than one-year-class every year and thatduring certain years several broods of the same year-class enter the fishery-Growth among juveniles was observed to be at a higher rate than among thebigger and older size groups. A special feature of the 1961-62 and 1962-63seasons was the entry on a large scale of smaller size groups ranging from 65 to85 mm into the fishery during August and September. Although oil sardineshoals occur within the 45 metre region, heavy concentrations were recordedin the 5 to 25 metre area.